2016
DOI: 10.1097/opx.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct Glare on Orbicularis Oculi and Trapezius During Computer Reading

Abstract: Results from the current study show that direct glare conditions cause increased eyestrain and orbicularis oculi contraction during reading on a computer screen. This study also indicates that exposure to direct glare affects the trapezius muscle, possibly by an interaction between the visual system, sympathetic nervous system, and head-stabilizing muscles. In addition, there were associations between the use of orbicularis oculi, trapezius blood flow, and development of neck pain independent of the lighting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 46 publications
7
24
0
Order By: Relevance
“…Glare is commonly experienced by computer users, has been found to reduce reading speed, and may also be a major cause of digital eye strain symptoms . The source of glare can be light from the visual display unit or from the surrounding environment, such as improper desk lighting .…”
Section: Symptoms and Risk Factorsmentioning
confidence: 99%
“…Glare is commonly experienced by computer users, has been found to reduce reading speed, and may also be a major cause of digital eye strain symptoms . The source of glare can be light from the visual display unit or from the surrounding environment, such as improper desk lighting .…”
Section: Symptoms and Risk Factorsmentioning
confidence: 99%
“…Increased psychological load has been shown to induce different physiological responses in humans; such as increased activity in the sympathetic nervous system, increased heart rate, decreased blink rate, and increased muscle activity and blood flow in trapezius and facial muscles (Hidaka et al 2004b ; Larsson et al 1995 ; Lundberg et al 2002 ; Nilsen et al 2007 ; Rodriguez et al 2018 ; Skoluda et al 2015 ). Some similar responses have been found to be induced by excessive light/glare, a visual stressor (Belkić 1986 ; Mork et al 2016 ; Saito et al 1996 ), suggesting that effects seen during exposure to visual stress also may involve a central mediated stress response.…”
Section: Introductionmentioning
confidence: 61%
“…The sample consisted of 43 healthy female undergraduate students recruited from the University College of Southeast Norway (Table 1 ). Sample size was calculated a priori with a test power of 80%, a significance level of 5% (two-tailed) and standard errors based on trapezius photopletysmography measurements from Mork et al ( 2016 ) (Owen 1962 ). Trapezius muscle blood flow was a main variable to investigate in the current study, and the power analysis showed that 36 participants should suffice to identify a 15% difference in trapezius blood flow between two repeated means, without and with glare exposure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations